Lu‘bah Tarkīb al-Qiṣah: Wasīlah Ta‘alīmiyyah Fa‘ālah li Tarqiyyati Mahārah al-Qirā’ah ladā Ṭalabah al-Madrasah al-Tsānawiyyah al-Islāmiyyah: Game Sequencing Stories: Effective Language Learning Media to Improve Reading Skills of Madrasah Aliyah Students - Achmad Fudhaili; Maswani; Siti Maisaroh (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2023)
This study aims to determine the effectiveness of "Sequencing Stories" as a medium of language games in improving the reading ability of MA AnnuqayahSumenep students. This type of research is quantitative, using a pre-experimental design with one group pre-test and post-test. The sample of this study amounted to thirty first-grade students. Data analysis was performed using paired sample T-Test. The results of this study indicate: (1) The procedure for applying the language game media "Sequencing Stories" consists of opening, core, and closing activities. Learning is carried out three times: delivery of vocabulary, reading, and practice. (2) The T-Test results show that the T-Count value is higher than the T-Table value. This shows that the alternative hypothesis (H1) is accepted, and the game is quite effective. This study's findings indicate that using the Sequencing Stories language game effectively improves students' reading skills. Keywords: Language Learning Media, Story Sequence Games, Reading Skills ملخص تهدف هذه الدراسة إلى تحديد فاعلية استخدام "تركيب القصة" كوسيلة للعبة اللغوية لترقية مهارة القراءة لدى طلبة مدرسة النقاية الثانوية الإسلامية سومنب. هذا النوع من البحث الكمي باستخدام تصميم ما قبل التجربة مع مجموعة واحدة قبل الاختبار وبعد الاختبار. بلغت عينة هذه الدراسة ثلاثين طالبا في الصف الأول. وتم إجراء تحليل البيانات باستخدام اختبار "ت" للعينة المزدوجة. تشير نتائج هذه الدراسة إلى أن: (1) إجراء تطبيق لعبة اللغة "تركيب القصة" يتكون من الأنشطة الافتتاحية والأساسية والختامية. ويتم عملية التعليم بثلاثة لقاءات وهي: توصيل المفردات، والقراءة، والتدريبات. (2) نتائج اختبار "ت" من النتيجة الحسابية أكبر من النتيجة الجدولية، هذا يدل على أن الفرضية البديلة (H1) مقبولة، وأن اللعبة فعالة للغاية. والحاصل إن نتائج هذه الدراسة تقول بأن استخدام لعبة "تركيب القصة" يحفز الطلبة على تعزيز تفاعلهم ومشاركتهم في عملية التعليم والتعلم. بالإضافة إلى ذلك، فقد أظهرت الدراسة فعالية هذه اللعبة في تعزيز كفاءة الطلبة في مهارة القراءة بشكل ملحوظ الكلمات المفتاحية: الوسائل التعليمية اللغوية، لعبة تركيب القصة، مهارة القراءة